Aktivasi BUMDes untuk Mendukung Upaya Mewujudkan Ketahanan Pangan Masyarakat di Desa Binuang Santang Kabupaten Balangan - Azzahra, Nabila; Budhi, Setia; Putri, Adellia Adzkia S.; Isaeraini, Vita; Anisa, Maulidia Nur; Hairina; Oktaviani, Reny Nurlita; Ayu, Linggar Meifirla; Hadri; Rizqin, Dhafin Mazaya; Setyawan, Ahmad Fery (Hayak Bamara: Jurnal Pengabdian Masyarakat, 2025)
The community service program implemented in Binuang Santang Village, Halong District, Balangan Regency, South Kalimantan, aims to reactivate the Village-Owned Enterprise (BUMDes) which had previously failed to develop its business. The community service team provided the community with knowledge on how to manage BUMDes by collaborating with external parties to provide input on the importance of community support for the businesses to be run. BUMDes had previously experienced failure and significant losses. This failure was caused by a series of fatal factors, including a lack of strategic planning, weak market risk analysis, and the lack of readiness of the management to run the business professionally, which became an important background for exploring strategies to activate BUMDes as a means of economic empowerment based on local potential. The service team applied the live-in method, which is staying at the service location with the aim of building more interaction with the community of Binuang Santang Village. The service was carried out for 58 days, from July 17, 2025, to September 12, 2025. The expected outcomes of the program include not only increased production but also increased collective income and strengthened village independence. Support from the community is the driving force behind ensuring that BUMDes provides broad benefits. Through the clear allocation of PADes, it not only improves economic welfare but also increases the quality of human resources (HR) in the village. Thus, BUMDes solidifies its position as an ideal model for inclusive development and ensures that the jobs created are stable and sustainable. BUMDes is a tangible manifestation of the philosophy that the village economy must be managed independently and professionally. In overcoming market challenges, technical training is key to optimizing infrastructure investments and transforming Binuang Santang from a food-producing village into a village that determines welfare.